Does the neighborhood built environment moderate the effectiveness of a weight-loss intervention for mothers with overweight or obesity? Findings from the Healthy Eating and Active Living Taught at Home (HEALTH) study - Amanda S. Gilbert; Deborah Salvo; Rachel G. Tabak; Debra Haire-Joshu (BMC, 2022)
Abstract Background Women of childbearing age are vulnerable to weight gain and experience a high prevalence of obesity due to pregnancy and stressors of parenthood. Lifestyle interventions such as the Healthy Eating and Active Living Taught at Home (HEALTH) study have been effective for weight loss; however, little is known about how the built environment (parks, transit, grocery stores, fast food, walkability etc.), where participants live might modify intervention effectiveness. This study examined whether characteristics of the neighborhood built environment modified effectiveness of the HEALTH study on weight loss.  Methods Secondary data analysis was conducted using data from HEALTH. Using GIS, buffers were built around participant addresses to capture distance to and availability of food (grocery store, convenience store, fast food) and urban design and transit (parks, street connectivity, transit) built environment characteristics. Built environment characteristics were dichotomized into low and high density and distance. Likelihood ratio tests for interaction were conducted to determine if built environment characteristics modified intervention effectiveness on Body mass index (BMI) and waist circumference (WC). Mixed effects linear regression models were then run to estimate the effect of the HEALTH intervention on weight outcomes at 24-months across both strata of built environment characteristics.  Results The analytic sample (n = 151) had baseline mean BMI 34.9 (SD = 5.8) and mean WC 46.0 cm (SD4.9). All urban design and transit and all food environment characteristics modified HEALTH effectiveness on one or both weight outcomes. The built environment modified the HEALTH intervention such that it was mostly effective for mothers residing in neighborhoods with low transit access, low street connectivity, high park access, and low access to grocery stores, convenience stores, and fast food. Conclusions Result show the HEALTH was most effective for women residing neighborhoods with built environment characteristics suggestive of suburban neighborhood typology. To maximize impact for mothers residing in all types of neighborhoods, future research should explore scaling up HEALTH in suburban settings, while adapting HEALTH to maximize effectiveness in compact neighborhoods most likely, urban core neighborhoods.